Colour demystified : a complete guide to mixing and using watercolours - Collins, Julie, 1962- (Search Press Limited, 2021)
"Unravel the mysteries of color and learn how to be more confident with your watercolour choices. Many painters are confused by their watercolour palettes and lack the confidence to experiment with color mixing. This book demystifies color, and helps artists understand how color works in a highly visual way through the use of color charts accompanied by examples, practical exercises, and analyses of watercolour paintings. Many painters are confused by their watercolor palettes and lack the confidence to experiment with color mixing. This book demystifies color, and helps artists understand how color works in a highly visual way through the use of color charts accompanied by examples, practical exercises, and analyses of watercolour paintings. Julie Collins helps you understand how color works in a highly visual way through the use of color charts accompanied by examples, practical exercises, and analyses of watercolor paintings, both her own works and those of contemporary artists. Topics such as granulation, iridescence, transparency and opacity are explained clearly and simply, to encourage you to experiment with colour and be altogether bolder and more creative. Numerous artworks by a variety of contemporary artists are featured in the book, covering a broad range of subjects and palettes. Topics such as granulation, iridescence, staining strength, and transparent and opaque colors will be explained clearly and simply, and there is practical guidance on colour relationships, using color to create space, and how to be more creative with color. Armed with a clearer understanding of color and how it looks and behaves on paper, artists will be encouraged to be more bold and creative in their use of color in their art"--Publisher's description.